Del's kitchen - Alfeche, David S., III; Bautista, Nilda Marie C.; Chavez, Mara Frances M.; Elizaga, Maria Elena M.; Nemiada, Angeli F.; Padilla, Jose Mari R.
Executive summary - Proponent description-The "Del's Kitchen" is a group of BM 239 students who would like to go into a business venture on selling "original" pancit molo balls. Through the years, the product has encountered so many changes --- changes in the style of cooking, changes in the manner the balls are wrapped, and changes in mixture of the molo balls themselves --- to suit individual taste. An attempt is now made to re-introduce the real taste of Pancit Molo, the way it was made and the way it should be since the time it vecome a "hit recipe" in the Molo District generations and generations ago. The group is composed of accountants and bankers, bonded by their desire to provide the consumers quality food which their money is worth. Headed by a cooking expert who has substantial knowledge on food, Nilda Bautista, the group decided to put their ideas into writing and validated the feasibility of that idea.